Examine the Importance of Amniotic Fluid Index (AFI) on Perinatal Outcome in Low Risk Term Pregnancy (Medical Forum Monthly, 2024)
Objective: Examine the clinical importance of low amniotic fluid index (AFI) on perinatal outcome in low risk pregnancy at term. Study Design: Prospective study Place and Duration of Study: This study was conducted at the Department of Obstetrics & Gynaecology, Sandeman Provincial Hospital Quetta from July 2018 to June 2019. Materials and Methods: One hundred and twenty patients were included. They were categorized into two groups; GroupA females having low amniotic fluid index ≤5 cm with term pregnancy admitted in labour room for delivery and Group B females with AFI >5 cm were selected as a control. Demographic details were recorded after written consent. Outcomes were examined such as NST measure, mode of delivery, Apgar score at 5 minutes, need to NICU, low birth weight, meconium aspiration and respiratory distress. Results: No significant difference observed between cases and controls regarding age of mother, non-stress test (NST) (reactive 81.67% vs 76.67%) and C-section delivery [30% vs 25%] (P>0.05). Significant difference was observed regarding Apgar score at 5 minutes <7 between both Groups (33.33% vs 8.33%) [P<0.05]. There was also a significant difference observed regarding need for admission to neonatal intensive care unit (8.33% vs 1.67), low birth weight (8.33% vs 1.67%) and meconium aspiration (11.67% vs 3.33%) between both groups (P<0.05). No perinatal death was recorded between cases and controls. Conclusion: We found no significant difference regarding NST and mode of delivery among both groups. However, patients with low AFI had a high rate of neonatal complications as compared to patients with standard AFI >5 cm.